Agricultural sustainability, growth, and poverty alleviation in East and South Asia : (Deutsche Stiftung für internationale Entwicklung, Zentralstelle für Ernährung und Landwirtschaft, 1997)
The book collects all papers presented at the Conference on agricultural sustainability, growth, and poverty alleviation in East and Southeast Asia. The papers discuss how best to promote "sustainable agricultural intensification" natural resource management that safeguards productivity of the natural resource base while meeting economic growth and poverty alleviation objectives... What are the ingredients for success in bringing natural resource management into the set of objectives for policymakers and researchers? Conference participants brought a range of country experiences and policy and research perspectives different economic development paths; different government roles in shaping those strategies; different institutions and mechanisms for government planning; different population densities, country sizes, natural resource richness, and level of food security to the table for four days in grappling with this question.